2012
DOI: 10.1590/s1806-83242012000300010
|View full text |Cite
|
Sign up to set email alerts
|

Rapid palatal expansion: a comparison of two appliances

Abstract: Rapid palatal expansion: a comparison of two appliancesAbstract: This study analyzed occlusal radiographs to compare the transverse changes produced in patients treated with rapid maxillary expansion using two types of appliances. The sample consisted of 31 children aged 7 to 10.6 years, of both genders, with posterior cross-bite. Fifteen children were treated with a tooth-borne expander and 16 were treated with a tooth-tissue-borne expander. Occlusal radiographs obtained at treatment onset and at the end of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 10 publications
(8 reference statements)
1
15
0
Order By: Relevance
“…The coronal parameter 1 evaluated the maxillary transverse dimension and showed numerical increases in both groups. These results corroborate other findings in the literature, which also report increase in skeletal transverse dimension after the RME (HAAS, 1970;RODRIGUES et al, 2012;SARVER;JOHNSTON, 1989). Nonetheless, only group 2 presented a statistically significant difference between the initial and final average.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The coronal parameter 1 evaluated the maxillary transverse dimension and showed numerical increases in both groups. These results corroborate other findings in the literature, which also report increase in skeletal transverse dimension after the RME (HAAS, 1970;RODRIGUES et al, 2012;SARVER;JOHNSTON, 1989). Nonetheless, only group 2 presented a statistically significant difference between the initial and final average.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have addressed the dentoskeletal effects of these expander appliances (AKYALCIN et al, 2013;ASANZA et al, 1997;BAYSAL et al, 2013;FARRONATO et al, 2008;GARIB et al, 2005;GARRETT et al, 2008;IWASAKI et al, 2014;LAGRAVÈRE et al, 2010;REED et al, 1999;RODRIGUES et al, 2012;SARVER;JOHNSTON, 1989), however, the comparison between them still remains controversial, especially regarding to the vertical effects. Some authors concluded that the bonded expander increases the transverse dimension of the maxilla, but limits or even eliminates changes in vertical dimension (ASANZA et al, 1997;SARVER;JOHNSTON, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…1 The difference between the tooth-borne and the tooth-tissueborne types of appliances is that the latter appliance has acrylic plates that cover the palatal mucosa bilaterally and is screw-retained with an 11-mm screw. 2 When the tooth-tissue-borne type of expander is used, the ulceration of the palatal mucosa may occur due to the acrylic part. In the presence of ulcers, symptoms such as swelling and pain can be present.…”
Section: Introductionmentioning
confidence: 99%
“…Transverse maxillomandibular discrepancies are a major cause of several malocclusions [ 2 ]. This type of malocclusion may be corrected in different manners, including slow expansion [ 3 , 4 , 5 ], rapid expansion [ 6 , 7 , 8 ], surgically assisted expansion [ 9 , 10 ] and miniscrew-assisted rapid palatal expansion (MARPE) [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%